Regarding Frank Capra : Audience, Celebrity, and American Film Studies, 1930-1960 - Smoodin, Eric Loren (Book collections on Project MUSE., 2004)
Using extensive archival research in fan mail, fan magazines, army services and educational records, Smoodin explores the different reception of Capra films with different popular audiences, and how the films meanings were marshalled to a variety of natio.